Index to word lists and comparative vocabularies - Seaward, Larry L., 1930- (Summer Institute of Linguistics, Institute of Nepal and Asian Studies, Tribhuvan University, 1974)
On Nepalese and Indian languages word lists published by the Summer Institute of Linguistics.